Quality of life analysis of medical students at a private university in Sergipe through the WHOQOL-bref: a sociodemographic approach (Research, Society and Development, 2021)
Objective: To analyze the quality of life and sociodemographic aspects of medical students in the first, eighth and twelfth period of a private higher education institution in Sergipe. Methods: This is a prospective cross-sectional analytical study involving medical students at a private university with the Problem Based Learning (PBL) teaching system. Two questionnaires were used, one sociodemographic and the World Health Organization's Quality of Life (WHOQOL-bref). Results: Of the total of 126 students, most are female, live with family members, never married and are aged between 20 and 35 years. In addition, most students do not work and pay their own tuition fees. The worst average in the analyzed domains was the psychological. In the sociodemographic aspect, significant values ​​were found, with lower averages of quality of life among those living in a private republic, those over 35 years of age, those who had the course financed and those who had a profession. Conclusion: According to the study, it is clear that there is a loss in the quality of life of medical students, with regard to sociodemographic factors, especially age, housing, form of payment for the course and work. Thus, it is important for the university to encourage leisure activities and publicize the Pedagogical and Psychosocial Support Center (NAPPS).